(untitled) (Med Phoenix, 2022)
Introduction: Abnormalities of any of the components of lacrimal function unit can lead to dysfunctional tear film and development of dry eye. Dry eye is a commonly encountered problem in general population. Materials and Methods: A hospital-based, case-control study was conducted at National Medical College and Teaching Hospital, Nepal from 1st August 2018 to 30th July 2019. A total of 279 participants: 93 cases of pterygium (Group A: case) and186 (Group B: control) normal individuals with no ocular surface disorder were enrolled. Objective analysis was done by Schirmer’s (SCH) without and with anesthesia and Tear Break up Time (TBUT). Dependent t test was used to analyze the data. P value <0.05 was considered statistically significant. Results: The mean age of the patients was 47.82 ±11.09 years (range 26-71) with male being 48 (51.6%) in Group A and in Group B, 101 (54.3%) were male with mean age being 42.16 ±13.13 years (range 32-75). The mean SCH without and with anesthesia and TBUT values were 16.94±5.61mm, 13.81±5.06mm, 10.14± 4.06 sec in Group A whereas in Group B, 20.39 ±6.08mm, 16.74 ±5.25mm and 13.05 ±4.32 sec respectively which was statistically significant (p < 0.05). Patients with pterygium had higher risk of having dry eye than normal individuals (Odd ratios: 2.69, 2.44 and 2.27 respectively). Conclusion: Pterygium is a common ocular surface disorder which could result in instability of tear film indices, dysfunctional tear film and thus dry eye.